IMPLEMENTASI SISTEM PENDUKUNG KEPUTUSAN DALAM PEMBERIAN BANTUAN KEPADA MASYARAKAT DESA - Lestari, Novia; Handayani, Reti; SY, Yulia Jihan (Jurnal Sains dan Informatika, 2017)
Salah satu langkah konkret yang dilakukan pemerintah dalam penanggulangan kemiskinan adalah dengan mengadakan program perlindungan sosial, yaitu berupa pemberian bantuan sosial kepada masyarakat miskin yang menjadi target sasaran program. Permasalahan yang sering terjadi dalam pelaksanaan program perlindungan sosial tersebut adalah terjadinya salah sasaran dalam pemberian bantuan sosial akibat adanya kesalahan (error) data, tidak akuratnya data penerima sasaran program perlindungan sosial, dan tidak konsistennya stake holder terkait dalam penentuan kelayakan masyarakat penerima bantuan. Maka dirancanglah sistem yang dapat membantu dalam perekapan, pengolahan, dan penyeleksian data penerima bantuan yaitu dengan sistem pendukung keputusan menggunakan metode Analytical Hierarcy Process (AHP) yang merupakan salah satu model untuk pengambilan keputusan yang komprehensif dengan memperhitungkan nilai bobot masing-masing kriteria. Sehingga bisa mempermudah stakeholder terkait dalam perekapan dan pengolahan data penerima bantuan, serta membantu dalam penentuan kelayakan penerima bantuan agar merata, tepat sasaran dan sesuai dengan ketentuan yang telah ditetapkan pemerintah.Â One of the concrete steps taken by the government in poverty alleviation is by conducting social protection program, which is social assistance to the poor targeted by the program. The problems that often occur in the implementation of social protection programs are the occurrence of misunderstandings in the provision of social assistance due to data errors, inaccurate data target beneficiaries of social protection programs, and inconsistent stakeholders related in determining the eligibility of beneficiary communities. Then the system is designed that can assist in the recording, processing and selection of beneficiary data that is with decision support system using Analytical Hierarcy Process (AHP) method which is one model for comprehensive decision making by calculating the weight value of each criterion. So that it can facilitate related stakeholders in recording and processing data of beneficiaries, and assist in determining the eligibility of beneficiaries to be equitable, right on target and in accordance with the provisions set by the governmentOne of the concrete steps taken by the government in poverty alleviation is by conducting social protection program, which is social assistance to the poor targeted by the program. The problems that often occur in the implementation of social protection programs are the occurrence of misunderstandings in the provision of social assistance due to data errors, inaccurate data target beneficiaries of social protection programs, and inconsistent stakeholders related in determining the eligibility of beneficiary communities. Then the system is designed that can assist in the recording, processing and selection of beneficiary data that is with decision support system using Analytical Hierarcy Process (AHP) method which is one model for comprehensive decision making by calculating the weight value of each criterion. So that it can facilitate related stakeholders in recording and processing data of beneficiaries, and assist in determining the eligibility of beneficiaries to be equitable, right on target and in accordance with the provisions set by the government.